The convergent roles and relationships of the actors in coastal resource management in the municipality of Guimaras. - Jancorda, Ma. Fatima V.
This is a descriptive study on the convergent roles and relationships of the actors in coastal resource management in Jordan, Guimaras. The study identified the laws and programs instituted for the CRM and the processes adopted by the local government in implementing them. The socio-economic situation of the municipality of Jordan as well as the coastal resource problems and concerns were discussed. Actors who played key roles in the CRM were identified together with the areas and aspects where they cooperated., Key informants of this study came from the offics of the actors (FARMC, Sangguniang Bayan Committee on Agriculture and Fisheries, MAO, BFAR, PENRO, Save the Children Foundation, and the fisherfolk organizations) identified through recorded interviews using unstructured questions. Several the same questions were asked from them as one of the data validation tools of the researchers. The result of the study showed that there is indeed a collaborative efforts among the actors from different agencies in the coastal management endeavor. The actors converge and work hand in hand for a successful implementation.